An improved EAAP scheme for vehicular ad hoc networks. (9th January 2020) - Gu, Tianlong; Yuan, Bin; Liu, Yining; Wang, Peng; Li, Long; Chang, Liang
Summary: Recently, Maria Azees et al proposed an "EAAP: efficient anonymous authentication with conditional privacy‐preserving scheme for Vehicular Ad Hoc Networks." Their scheme is mainly to solve the problem of high computation time of anonymous certificate and signature authentication, as well as the tracking problem of malicious vehicles. However, some improvements are needed in the protection of anonymous identity and the effective tracking of malicious vehicles. In this paper, our scheme realizes mutual authentication between OBU and RSU, and the RSU is authenticated without using certificate. In order to prevent the anonymous identity of the vehicles from being monitored and tracked, we use the negotiated short‐time key to encrypt the anonymous identity in the vehicle certificates. In addition, our scheme uses a new tracking method for malicious vehicles. Then, we prove the scheme through BAN logic, and it has the properties of authentication, anonymity, unlinkability, privacy protection, and traceability. Finally, we compare the computation cost and communication cost with other schemes, and the scheme has been greatly improved. Abstract : In order to solve the security problems of EAAP scheme, we propose an improved EAAP scheme for vehicular ad hoc networks. Then, we analyze the computation cost and communication cost of the scheme and compare it with TAA, SPRING, ECPB, and EAAP scheme in detail. Finally, we conclude that the scheme has greatly improved in the signature, authentication, and communication phases.